2014
DOI: 10.1530/joe-14-0391
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia has no effect on development of restenosis after percutaneous transluminal angioplasty (PTA) in a diabetic rabbit model

Abstract: It is well known that hyperglycemia is a trigger of atherosclerosis in patients with diabetes mellitus. However, the role of hyperglycemia in restenosis remains unclear. In this study, we investigated the effects of hyperglycemia on restenosis. Stenosis was evaluated in two sets of diabetic rabbit models: i) diabetic restenosis versus nondiabetic restenosis and ii) diabetic atherosclerosis versus nondiabetic atherosclerosis. Our results indicated that there was no difference in rates of stenosis between the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 23 publications
3
11
0
Order By: Relevance
“…To the best of our knowledge, there are few studies on the pathogenesis of restenosis after LEAD. Our previous studies found a unique mechanism of restenosis which was in consistence with others 22,23 and demonstrated that the excessive proliferation and migration of VSMCs from the media to the intima were the main cause of restenosis 8 . In the present study, the potential pathogenesis was further investigated and we found that Lin28a played a crucial role in regulating the proliferation and migration of VSMCs in restenosis.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…To the best of our knowledge, there are few studies on the pathogenesis of restenosis after LEAD. Our previous studies found a unique mechanism of restenosis which was in consistence with others 22,23 and demonstrated that the excessive proliferation and migration of VSMCs from the media to the intima were the main cause of restenosis 8 . In the present study, the potential pathogenesis was further investigated and we found that Lin28a played a crucial role in regulating the proliferation and migration of VSMCs in restenosis.…”
Section: Discussionsupporting
confidence: 84%
“…The rats were allowed to adapt to the new environment for at least 7 days, and then were fed with a high‐fat diet during the whole experiment. The animal care and experiments were in conformity to the previous publication 8 . The protocol was authorized by the ethical committee of Qianfoshan Hospital Affiliated to Shandong University.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction of experimental diabetes mellitus: after an overnight fasting, 80 mg/kg of freshly prepared alloxan solution was injected intravenously from the marginal ear vein of rabbits [ 10 ]. Animals had free access to food and water after the alloxan injection, and an oral solution of 20 % glucose was provided after confirmation of hypoglycemia to prevent hypoglycemic shock.…”
Section: Methodsmentioning
confidence: 99%
“…One week after diabetes induction, rabbits were anesthetized with phenobarbital. An arteriotomy in the right saphenous artery was made with standard surgical techniques, then a 2.5-mm, wire-guided balloon catheter was inserted and the iliac artery injury was made as previously described [ 10 ] (Fig. 1a ).…”
Section: Methodsmentioning
confidence: 99%